2019
DOI: 10.1002/ijc.32583
|View full text |Cite
|
Sign up to set email alerts
|

Distinct HR expression patterns significantly affect the clinical behavior of metastatic HER2+ breast cancer and degree of benefit from novel anti‐HER2 agents in the real world setting

Abstract: Additional Supporting Information may be found in the online version of this article.Impact of HR expression on the outcomes of metastatic HER2+ breast cancer treated with novel anti-HER2 agents Int.Cancer Therapy and Prevention other agents (7 vs. 6 months, p = 0.03). There was no PFS2 gain in patients with tumors expressing both hormonal receptors (HRs; p = 0.17), while a trend emerged for tumors with one HR (p = 0.05). Conversely, PFS2 gain was significant in HRsnegative tumors (p = 0.04). Median overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Moreover, we found that, when compared to the older patient cohort, younger patients were not only more likely to be HER2-positive, but also more likely to present with triple-positive disease (Table 1 ). Triple positive breast tumors constitute an emerging class of BC, that is increasingly demonstrating distinctive resistance patterns to both anti-HER2 targeting drugs and other endocrine therapies 23 , 24 . To our knowledge, this is the first study to portray a difference in the rate of the triple-positive tumor subtype between young and old BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that, when compared to the older patient cohort, younger patients were not only more likely to be HER2-positive, but also more likely to present with triple-positive disease (Table 1 ). Triple positive breast tumors constitute an emerging class of BC, that is increasingly demonstrating distinctive resistance patterns to both anti-HER2 targeting drugs and other endocrine therapies 23 , 24 . To our knowledge, this is the first study to portray a difference in the rate of the triple-positive tumor subtype between young and old BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study performed interaction analyses and both types of subgroup analyses for time-to-event as well as binary endpoints [ 30 ]. Eight studies showed only results from subgroup analyses: 3 evaluated the treatment effect by biomarker subgroups [ 42 44 ], 4 the biomarker effect by treatment subgroups [ 46 49 ] and 1 only presented Kaplan-Meier curves for recurrence-free survival for all biomarker-treatment combinations [ 50 ]. Thus, there were 20, 7 and 1 studies that performed subgroup analysis for treatment effect by biomarker subgroup, biomarker effect by treatment subgroup and all biomarker-treatment subgroups, respectively (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bahceci et al included subgroups for patients receiving 1L, 2L and 3L+ is reported in each separate section [ 42 ]. Pizzuti 2020 reported subgroup populations for 1L and 2L [ 48 ]. The RCTs were either phase II (n = 2) or phase III trials (n = 3) and conducted in multinational settings with sample sizes ranging from 210 to 1092 patients ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven observational studies on patients with HER2+ a/mBC receiving 2L SOC were included in this SLR [ 42 , 48 , 56–60 ] and were conducted in different countries (Turkey [n = 1], Italy [n = 4], Japan [n = 1] and Spain [n = 1]). Fabi 2017b reported subgroups for patients receiving 2L and 3L+, thus the study is reported in both sections [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation